Comparative electoral processes in South Asia - Panday, Devendra Raj.; Aditya, Anand; Dahal, Dev Raj.; Nepal South Asia Centre (Kathmandu, Nepal); Workshop on Electoral Processes in South Asia 1999 : Kathmandu, Nepal) (Kathmandu : Nepal South Asia Centre, 1999)
Papers and proceedings of the Second Workshop on Electoral Processes in South Asia held in Kathmandu and organised by Nepal South Asia Centre in February 1999.
Keywords: Elections -- South Asia -- Congresses; Representative government and representation -- South Asia -- Congresses; Comparative government -- Congresses